Effect of the coexistence of nitrogen compounds on the sulfur tolerance and catalytic activity of Pd and Pt monometallic catalysts supported on high-silica USY zeolite and amorphous silica - Matsui, Takashi; Harada, Masaru; Toba, Makoto; Yoshimura, Yuji (Applied catalysis. A, General, 2005)
The effects of coexistence of nitrogen compounds on the catalytic activity of the Pd and Pt monometallic catalysts supported on amorphous silica and high-silica USY zeolite (SiO 2/Al 2O 3 = 390) were investigated using a high-pressure fixed-bed continuous flow reactor operating at 3.9 MPa and 553 K. Types of catalytic activity studied included the tetralin hydrogenation activity and the 4,6-dimethyldibenzothiophene (4,6-DMDBT) hydrodesulfurization activity. The Pd/USY zeolite catalyst showed the highest tetralin hydrogenation activity with feedstock containing only 4,6-DMDBT ( S = 300 ppm) without nitrogen compounds. However, its hydrogenation activity was strongly inhibited by the addition of n-butylamine ( N = 20 ppm). Significant inhibitory effects by nitrogen compounds were also observed for the Pd/SiO 2 catalyst. The Pt/USY zeolite catalyst showed lower hydrogenation activity than the Pd/USY zeolite, while the Pt/SiO 2 catalyst showed higher activity than the Pd/SiO 2 catalysts. The inhibitory effects of nitrogen compounds on these Pt catalysts were less pronounced than on Pd catalysts. On the other hand, with respect to hydrodesulfurization, Pt catalysts showed higher activity in 4,6-DMDBT hydrodesulfurization than Pd catalysts, irrespective of the support species, due to the latter's higher hydrogenolytic ability to cleave the C S bond even in the presence of nitrogen compounds. On the other hand, Pd catalysts were subject to a decrease in 4,6-DMDBT hydrodesulfurization resulting from a loss in hydrogenation activity in the presence of nitrogen compounds. We conclude that Pt catalysts are superior to Pd catalysts with respect to both hydrogenation and hydrodesulfurization for the hydrotreatment of industrial feedstocks containing sulfur and nitrogen compounds.